Radio-frequency connectors. Part 61: Sectional specification for RF coaxial connectors with 9, 5 mm inner diameter of outer conductor, quick lock coupling, series Q4.1-9.5 Part 61, (28th July 2020) - British Standards Institution,
No abstract available